2010
DOI: 10.1007/s12028-010-9477-4
|View full text |Cite
|
Sign up to set email alerts
|

Osmotherapy: Use Among Neurointensivists

Abstract: Treatment of cerebral edema using osmotically active substances varies considerably between practitioners. This variation could hamper efforts to design and implement multicenter trials in neurocritical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 42 publications
0
36
0
3
Order By: Relevance
“…A recently published meta-analysis considering 112 patients of 5 trials describe an advantage for hypertonic therapy in comparison to mannitol in order to control elevated ICP with a mean difference of 2 mm Hg [20]. In general, more neurointensivists favor the use of hypertonic saline for a reduced frequency of rebound edema, less side effects, desired volume expansion, and a longer-lasting duration of therapeutic effects [21]. Furthermore, therapeutic hypothermia (33°) offers a neuro-protective and anti-edematous therapy with proven efficiency in animal models and clinical trials after global ischemia, albeit proof of efficiency is still lacking for focal cerebral ischemia [22,23,24].…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…A recently published meta-analysis considering 112 patients of 5 trials describe an advantage for hypertonic therapy in comparison to mannitol in order to control elevated ICP with a mean difference of 2 mm Hg [20]. In general, more neurointensivists favor the use of hypertonic saline for a reduced frequency of rebound edema, less side effects, desired volume expansion, and a longer-lasting duration of therapeutic effects [21]. Furthermore, therapeutic hypothermia (33°) offers a neuro-protective and anti-edematous therapy with proven efficiency in animal models and clinical trials after global ischemia, albeit proof of efficiency is still lacking for focal cerebral ischemia [22,23,24].…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…A recent publication surveyed members of the Neurocritical Care Society and found that while 90% of members used hyperosmolar agents for refractory elevated ICP, 55% preferred hypertonic saline to mannitol. 31 Our recent systematic review 59 on hyperosmolar agents in aSAH revealed 2 randomized studies examining the effect of hypertonic saline on ICP in aSAH. Huang and Yang 39 found no difference between mannitol and hypertonic saline in controlling refractory raised ICP ≥ 20 mm Hg.…”
Section: Hyperosmolar Agentsmentioning
confidence: 99%
“…Consequently, close monitoring of the patients' ICP, CPP, serum sodium, and serum osmolarity is required. Despite the lack of convincing evidence, general consensus it that driving the serum sodium above 160 mEq/L is rarely beneficial, and most clinicians try to maintain the serum osmolarity below 320 mOsm/L (Hays et al 2011). When intracranial hypertension persists despite maximal osmotherapy, ICP may be controlled by interventions designed to decrease the cerebral blood volume.…”
Section: Cerebral Edema Intracranial Hypertension and Cerebral Perfumentioning
confidence: 99%